Why do Consumers Adopt E-Grocery? A Systematic Literature Review - Dea Wemona Rahma; Sasmi Hidayatul Yulianing Tyas; Qilbaaini Effendi Muftikhali (Journal of Informatics and Communication Technology (JICT), 2022)
Electronic grocery (e-grocery) is currently the most emerging subset of online shopping. Every week, 28.3% of people buy grocery products online. The value of e-grocery sales in Indonesia is predicted to continue to rise and will reach around US $5.6 trillion by 2026. This indicates that e-grocery is an important potential market for quick-commerce online shopping services in the future. A Systematic Literature Review research in the field of e-grocery has existed before. A Systematic Literature Review research in the field of e-grocery has existed before. However, to date, the authors have not found SLR research that focuses on exploring the driving factors of e-grocery adoption. To bridge the gap, the purpose of this study is to provide a comprehensive overview of the factors that influence consumers to adopt e-grocery or online grocery shopping. The method used was Systematic Literature Review. The process of searching and selecting scientific articles through Scopus with various criteria resulted in 25 primary studies. The results showed that the most common driving factors found among the 25 studies were Perceived Ease of Use and Perceived Usefulness adapted from TAM theory, delivery time factor, and demographic factors such as age, gender, income, and education level. Despite the numerous factors mentioned in the primary studies, no factor has been able to represent the phenomenon of deals and promotions that are often found in various e-commerce applications, including e-grocery service providers.